FARINHA DE JENIPAPO NA DIETA DE JUVENIS DE PACU - MENEZES, José Samuel Pereira; VIEIRA, Gleice Kelli; SILVA, Leonardo Augusto; OLIVEIRA, Fúlvia Cristina; PASQUETTI, Tiago Junior; CAMPOS, Cristiane Meldau (ANAIS DO ENIC, 2018)
-